SCREEN HOUSE TEST OF EIGHT BIOPESTICIDE FORMULATION BACILLUS SUBTILIS AGAINST DOWNY MILDEW, PERONOSCLEROSPORA PHILIPINENSIS, ON CORN PLANT - Djaenuddin, Nurasiah; Muis, Amran; Nonci, Nurnina (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Screen House Test of Eight Biopesticide Formulation Bacillus subtilis against Downy Mildew, Peronosclerospora philipinensis, on Corn Plant. Corn downy mildew (DM) caused by Peronosclerospora spp. is a major constraint to the decline in maize production because it can cause yield loss up to 100%. So far, DM was successfully controlled with metalxyl fungicide. But lately, the effectiveness of this fungicide has begun to decline, so there is a need for an appropriate and environmentally friendly control alternative, one of which is the use of biological control agents. The aim of this study was to know the influence of eight types of biopesticide formulation of Bacillus subtilis in controlling DM of corn plant. The study was conducted at the screenhouse of the Indonesian Cereals Research Institute at Maros from November to December 2016. The treatments were arranged in a randomized block design with nine treatments and three replications. The treatment consisted of seed treatment with eight types of B. subtilis formulations (TM4, TM3, BNt4, BNt5, BNt6, BNt8, BJ6, and TLB1) and one treatment with sterile water (control). The variety used was Anoman which is known to be highly susceptible to DM. The variables observed included number of germination, the incidence and incubation period of disease, plant height, and dry weight of the plant. The results showed that the eight B. subtilis formulations had the potential to suppress DM in corn. The symptom of DM began to be seen at 18 days after planting (DAP) on the treatment of BNt8, while the controls have been seen at 12 HST. B. subtilis TM formulation has the highest potential to suppress DM with the percentage of disease suppression reaching 63.1%.